2016
DOI: 10.1002/ijc.30154
|View full text |Cite
|
Sign up to set email alerts
|

Record linkage to correct under‐ascertainment of cancers in HIV cohorts: The Sinikithemba HIV clinic linkage project

Abstract: The surveillance of HIV‐related cancers in South Africa is hampered by the lack of systematic collection of cancer diagnoses in HIV cohorts and the absence of HIV status in cancer registries. To improve cancer ascertainment and estimate cancer incidence, we linked records of adults (aged ≥ 16 years) on antiretroviral treatment (ART) enrolled at Sinikithemba HIV clinic, McCord Hospital in KwaZulu‐Natal (KZN) with the cancer records of public laboratories in KZN province using probabilistic record linkage (PRL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 28 publications
4
38
3
Order By: Relevance
“…Cohorts from the following IeDEA regions initially contributed data to our study: the North American AIDS Cohort Collaboration on Research and Design (NA‐ACCORD), the Caribbean, Central and South America network for HIV epidemiology (CCASAnet), IeDEA Southern Africa, and IeDEA Asia‐Pacific . For the IeDEA Southern Africa region, we restricted the analysis to two cohorts from South Africa that reduced under‐reporting of cancer cases in the HIV cohorts through record linkages with the National Cancer Registry . COHERE is a collaboration of observational HIV cohorts across Europe .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohorts from the following IeDEA regions initially contributed data to our study: the North American AIDS Cohort Collaboration on Research and Design (NA‐ACCORD), the Caribbean, Central and South America network for HIV epidemiology (CCASAnet), IeDEA Southern Africa, and IeDEA Asia‐Pacific . For the IeDEA Southern Africa region, we restricted the analysis to two cohorts from South Africa that reduced under‐reporting of cancer cases in the HIV cohorts through record linkages with the National Cancer Registry . COHERE is a collaboration of observational HIV cohorts across Europe .…”
Section: Methodsmentioning
confidence: 99%
“…12 For the IeDEA Southern Africa region, we restricted the analysis to two cohorts from South Africa that reduced underreporting of cancer cases in the HIV cohorts through record linkages with the National Cancer Registry. 13 COHERE is a collaboration of observational HIV cohorts across Europe. 14 It contributed data from 24 cohorts, covering 36 countries.…”
Section: Databasesmentioning
confidence: 99%
“…There are severe deficits in cancer registration in LMIC, particularly SSA and even for registries contributing to WHO global cancer estimates, including low population coverage, significant urban bias, and low data quality [7**]. Even in well enumerated HIV cohorts retained in care on chronic ART, ascertainment of cancer diagnoses is poor [8*]. Diagnostic pathology in SSA is also limited, and often under-utilized when it exists [9].…”
Section: Epidemiologymentioning
confidence: 99%
“…Few other studies reported similarly high ICC incidence rates in HIV-positive women, 26,28,31 but most studies found substantially lower ICC incidence rates. [19][20][21][22]29,[32][33][34][35][36] For example, in a cohort of regularly Pap-screened HIV-positive women in the United States, the ICC incidence rate was as low as 12/100,000 pys. 36 Whereas well-established systematic screening programs might partly explain the lower ICC incidence rates in HIV-positive women living in high-income countries, the very low ICC incidence rates found in three sub-Saharan African record linkage studies are likely to be underestimations.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…17,18 To inform cervical cancer screening programs for HIV-positive women in South Africa, data on ICC burden, associated risk factors, and the effect of screening programs on ICC risk in this specific population are needed. Whereas some ICC incidence rate estimates are available for HIV-positive women in sub-Saharan Africa, ranging from 8/100,000 pys to 259/100,000 pys, [19][20][21][22] data on risk factors and the effect of cervical cancer screening on ICC risk are scarce for the African setting. Studies examining the effect of cervical cancer screening at the patient-level often do not have enough power to detect changes in ICC incidence rates.…”
mentioning
confidence: 99%